Microdochium majus Isolated from Grapevine Is a Mycoparasite of Botrytis cinerea - Kálmán Zoltán Váczy; Dóra Szabó; Nikolett Molnár; Tibor Kiss; Levente Kiss; Yu Pei Tan; Ádám Novák; Xénia Pálfi; Adrienn Gomba-Tóth; Zoltán Karácsony (Journal of Fungi)
The best known Microdochium spp. are important pathogens of small-grain cereals and/or endophytes of diverse monocot hosts. This study is the first report of M. majus isolated from asymptomatic grapevine tissues. It was hypothesised that this M. majus strain, CBS 152328, was an endophyte and an antagonist of some fungal pathogens of grapevine. Microscopic examinations revealed that this strain was a necrotrophic mycoparasite of Botrytis cinerea. This was demonstrated in the confrontation zones of dual cultures of M. majus and B. cinerea, and also on the surface of co-inoculated grape leaf discs and germinated wheat grains. Pathogenicity tests indicated that M. majus can colonise both grape leaf discs and germinated wheat, but it only damaged wheat. When co-inoculated with B. cinerea onto grape leaf discs, the M. majus strain CBS 152328 suppressed its mycohost on grape tissues and prevented leaf necrosis caused by B. cinerea. In addition to the parasitism, M. majus also showed mild antibiosis against B. cinerea, as well as a defence elicitor effect on grape leaf discs. This work is the first report of the mycoparasitic behaviour of M. majus, in addition to its first isolation from a dicot host.